Analysis of wheel pairs slip control of electric freight locomotive with asynchronous traction motors - A. N. Savos’kin; N. D. Shilin (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Every year, the amount of electric rolling stock with asynchronous traction motors is continuously increasing on the Russian railway network, since such traction drives have a number of advantages over drives with DC motors. One of the problems associated with the introduction of asynchronous motors and an increase in the mass of trains is the implementation of the maximum traction force by an electric locomotive at the threshold in terms of wheel – rail adhesion. Timely recognition of excessive slip of wheel pairs is the most important indicator of the efficiency of the traction drive in realising the maximum traction properties of the electric locomotive at all axles.Materials and methods. The article reflects the results of the study of slip of electric locomotive wheel pairs with asynchronous traction motors and axial control of the traction force, obtained during experimental runs on a railway section under various adhesion conditions. The article presents a technique for studying the wheel pair adhesion failure of electric locomotives with asynchronous traction motors.Results. During the comparison of the obtained experimental results with the calculated parameters by the O. Polach mathematical model, an updated range of the relative slip of wheel pairs is given, in which the electric locomotive control system could realise the maximum tractive effort. Exceeding this range will lead to increased wear of wheel pairs without increasing traction properties.Discussion and conclusion. It is advisable to use the results of the study in the future when developing systems for controlling the tractive effort at the limit of adhesion and systems for controlling the slip of wheel pairs of electric freight locomotives with asynchronous traction motors.